2020
DOI: 10.1021/acsami.0c04297
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar Charge Transport in Two-Dimensional WS2 Metal–Insulator–Semiconductor and Metal–Insulator–Semiconductor Field-Effect Transistors

Abstract: Two-dimensional (2D) materials with ambipolar transport characteristics have attracted considerable attention as post-complementary metal−oxide semiconductor (CMOS) materials. These materials allow for electron-or hole-dominant conduction to be achieved in a single channel of the field-effect transistors (FETs) without an extrinsic doping. In this study, all-2D metal−insulator−semiconductor (MIS)-based devices, which were composed of all-2D graphene, hexagonal boron nitride, and WS 2 , exhibited ambipolar and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Indeed, some examples of WS2-based devices fabricated in typical CMOS BEOL conditions have already been reported: Yang and co-workers [34] have demonstrated a WS2-based alloptical modulator fully integrated with typical CMOS Si3N4 waveguides to modulate a 532 nm pump light source. Moreover, a fully CMOS-compatible graphene-hBN-WS2 metal-insulator-semiconductor transistor showing ambipolar behaviour has also been recently reported [35]. These early results confirm that the optimization of WS2-Si chips can be boosted by employing already-optimized CMOS BEOL fabrication steps, rather than implementing a completely new protocol.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Indeed, some examples of WS2-based devices fabricated in typical CMOS BEOL conditions have already been reported: Yang and co-workers [34] have demonstrated a WS2-based alloptical modulator fully integrated with typical CMOS Si3N4 waveguides to modulate a 532 nm pump light source. Moreover, a fully CMOS-compatible graphene-hBN-WS2 metal-insulator-semiconductor transistor showing ambipolar behaviour has also been recently reported [35]. These early results confirm that the optimization of WS2-Si chips can be boosted by employing already-optimized CMOS BEOL fabrication steps, rather than implementing a completely new protocol.…”
Section: Introductionmentioning
confidence: 59%
“…Similarly to graphene, TMDs can be monolithically integrated with well-established CMOS BEOL [28]. Indeed, TMDs-Si chips have already been reported for a number of applications [29,[31][32][33][34][35]. This compatibility gives to TMDs a great advantage in terms of process optimization and cost reductions with respect to other "beyond-CMOS" candidates, such as III-V semiconductors or Ge, in which indirect integration with Si chips is much more challenging [36].…”
Section: Introductionmentioning
confidence: 99%
“…Through the above circuit structure engineering, many efforts were made to fabricate CMOS-like circuits with ambipolar 2D semiconductors. [267] Using graphene as the channel material and 300 nm thick SiO 2 as dielectric, Traversi et al demonstrated an inverter but the operating voltage was a little high (10 V) and the voltage gain was very low (only 0.044). [268] Li et al further improved the circuits with aluminum film as top gate, where the natural passivation layer between the graphene and aluminum served as dielectric.…”
Section: Circuits Structure Engineeringmentioning
confidence: 99%
“…Complementary metal-oxide semiconductors (CMOS) logic circuits lay the foundation of modern electronics, where both p-type (hole transport) and n-type (electron transport) conjugated-polymers, in which both holes and electrons are allowed to transport, [18][19][20][21][22][23][24][25] are employed to fabricate ambipolar transistors with multiple operations to simplify the fabrication process of CMOS-like logics and miniaturize the integrated circuits. [19] Moreover, ambipolar transistors are more favorable for building reconfigurable electronics and endowing the circuits with multi-functionalities.…”
Section: Introductionmentioning
confidence: 99%